Private Boarding Houses at Aparri: A Home Away From Home? - L. Malana, Matilde; S. Javier, Billy (International Journal of Psychosocial Rehabilitation, 2020)
The safety and welfare of the students of Cagayan State University (CSU) at Aparri is the primary concern of the Office of the Student Development and Welfare (OSDW). The need to determine the profile and status of the boarding houses was the main objective of this study including the profile of the student-boarders as well as the status on the physical, social and environmental condition of the private boarding houses in Aparri Cagayan Philippines. Descriptive-survey method was employed involving 1,503 student-boarders enrolled for the school year 2015-2016. Secondary data were taken through document reviews and interviews to home owners. In general, student-boarders come to an agreement that the private boarding houses in Aparri along physical, social, and economic are in good condition. Basic amenities were provided, but in a limited extent. On social conditions, harmonious relationship among boarders, and with house owners is practiced. Economically, boarding houses in Aparri were found affordable and additional charges are reasonable. Hence, the private boarding houses at Aparri proved to be a home away from home. It is recommended that the OSDW should regularly monitor all boarding houses in coordination with the Local Government Unit of Aparri for stronger alliance and legal support.